Building Praise: Augustan Rome and Epideictic. Issue 2 (4th May 2019) - Lamp, Kathleen S.
ABSTRACT: In this essay, I examine two epideictic artifacts from the Roman Principate, The Res Gestae Divi Augusti and the summi viri, arguing Augustus used them to reshape the model of a good leader, in part, by emphasizing contributing to the built environment of the city. Additionally, the public and visual nature of these artifacts made them highly accessible to those outside of the Roman elite, who may have sought social mobility through the imperial bureaucracy allowing for more diverse participation in the Roman government. I close by considering the influence of classical exemplars on U.S. civic spaces.